2019
DOI: 10.2458/lymph.4620
|View full text |Cite
|
Sign up to set email alerts
|

Early Fetal Hydropic Changes Are Associated With Moderate Dilatation of the Brain Ventricular System: A Clue to a Possible Link Between Cervical Lymphatic Engorgement and Ventricular Dilatation?

Abstract: The aim of this study is to assess whether early cervical lymphatic obstruction is associated with a sonographically detectable dilatation of the ventricular system in the 1st trimester of pregnancy. In particular, the objective is to assess whether fetuses with non-immune hydrops fetalis (NIHF), cystic hygroma, or enlarged nuchal translucency (NT) have a greater atrial width/biparietal diameter (AW/BPD) ratio than normal at time of the combined first trimester screening scan. This retrospective study included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Zhou LX et al [ 9 ] and Wagner M et al [ 10 ] reported that the internal jugular veins dilated when the fetuses had a vein of Galen aneurysmal malformation (VGAM), while other authors reported that the internal jugular vein blood flow of fetuses with increased nuchal translucency [ 11 ] or intrauterine growth restriction [ 12 ] was higher than that of normal fetuses. When fetal oedema is accompanied by ventricular dilation and cervical lymph node enlargement, the internal jugular veins will also present with secondary changes [ 13 ]. Dilation or stenosis of the internal jugular veins often occurs in fetuses with congenital heart disease [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou LX et al [ 9 ] and Wagner M et al [ 10 ] reported that the internal jugular veins dilated when the fetuses had a vein of Galen aneurysmal malformation (VGAM), while other authors reported that the internal jugular vein blood flow of fetuses with increased nuchal translucency [ 11 ] or intrauterine growth restriction [ 12 ] was higher than that of normal fetuses. When fetal oedema is accompanied by ventricular dilation and cervical lymph node enlargement, the internal jugular veins will also present with secondary changes [ 13 ]. Dilation or stenosis of the internal jugular veins often occurs in fetuses with congenital heart disease [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%